The implementation of a portfolio to improve the written use of present perfect tense in a case study of a 2nd year student of bachillerato, in parallel A at Vicente Anda Aguirre high school, academic year 2013-2014 - Campoverde Jumbo, Angela Cecilia (2015)
This case study had the purpose to improve the written use of present perfect tense with the implement of portfolio with a 2nd year student of Bachillerato at Vicente Anda Aguirre High School. An intervention plan with eight sessions was carried out to improve the learning of present perfect tense. Researcher’s-made tests were designed and used to measure the student´s progress. Instruments like field diary were also used every session to see the student´s progress. The results indicated that the use of portfolio facilitated meaningfully the student’s progress which was reflected in the noticeable increase of the posttest scores. The notes recorded in the field diary also confirmed the enthusiasm and the positive attitude toward working with the portfolio. It is to concluded that this study helped the student to overcome the issues, the researcher to sharpen her teachings skills and the community to have a well-prepared candidate teacher.